Exploring the impact of farmer-led research supported by civil society organizations - Waters-Bayer, Ann; Kristjanson, Patricia M.; Wettasinha, C; Veldhuizen, L. van; Quiroga, G; Swaans, Cornelis P.M.; Douthwaite, Boru (Springer, 2015)
This paper asks: What have been the impacts of farmer- or community-led (informal) processes of research and development in agriculture and natural resource management in terms of food security, ecological sustainability, economic empowerment, gender relations, local capacity to innovate and influence on formal agricultural research and development institutions? An innovative conceptual framework was applied to a diverse set of farmer-led research initiatives in countries in Africa, Asia and Latin America to explore approaches, outcomes and impacts of informal agricultural research and development (ARD) facilitated by civil society organisations. Findings include the following: locally appropriate technical innovations emerging from these processes are readily taken up by other farmers; the most common channels of dissemination are farmer to farmer through informal networks and spaces created for farmer-researchers and other farmers to meet and exchange, such as innovation fairs; livelihood impacts are broad and substantial; local capacity to innovate is strengthened and institutionalisation through the formal sector has been limited. Lessons are drawn for future partnerships in promoting and supporting farmer-led research involving formal and informal ARD actors working with smallholder communities.